A 'Universal' Density Profile for the Outer Stellar Halos of Galaxies. Issue Volume 11:Issue S321(2015) (21st March 2017) - Remus, Rhea-Silvia; Burkert, Andreas; Dolag, Klaus
Abstract: The outer stellar halos of galaxies contain vital information about the formation history of galaxies, since the relaxation timescales in the outskirts are long enough to keep the memory, while the information about individual formation events in the central parts has long been lost due to mixing, star formation and relaxation. To unveil some of the information encoded in these faint outer halo regions, we study the stellar outskirts of galaxies selected from a fully hydrodynamical high-resolution cosmological simulation, called Magneticum. We find that the density profiles of the outer stellar halos of galaxies over a broad mass range can be well described by an Einasto profile. For a fixed total mass range, the free parameters of the Einasto fits are closely correlated. Galaxies which had more (dry) merger events tend to have lesser curved outer stellar halos, however, we find no indication that the amount of curvature is correlated with galaxy morphology. The Einasto-like shape of the outer stellar halo densities can also explain the observed differences between the Milky Way and Andromeda outer stellar halos.